2018
DOI: 10.3390/ijerph15112512
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Sleep Quality Are Associated with Physical Activity in Elderly People Living in Nursing Homes

Abstract: The main purpose of the study was to explore the associations of sleep duration and sleep quality with physical activity (PA). In this cross-sectional study, participants were 894 elderly individuals (mean age 80 ± 3 years; 56.0% women) living in nursing homes. PA, sleep duration, and sleep quality (based on the Pittsburgh Sleep Quality Index (PSQI)) were self-reported. The associations of sleep duration and sleep quality with PA at the nursing home level were analyzed using generalized estimating equations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 31 publications
4
35
1
3
Order By: Relevance
“…This finding is comparable to those of other previous studies conducted in elderly adults living in nursing homes in Turkey [31,32]. However, with a similar population, the same institutional setting and measurement tool, Stefan et al [33] found that 54.5% of individuals were poor sleepers among 894 elderly adults in Zagreb nursing homes. Tsai et al [34] found that 46.4% of participants reported poor sleep quality among 196 elderly AOR, adjusted odds ratio; RERI, the relative excess risk due to interaction; AP, the attributable proportion due to interaction; S, the synergy index.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is comparable to those of other previous studies conducted in elderly adults living in nursing homes in Turkey [31,32]. However, with a similar population, the same institutional setting and measurement tool, Stefan et al [33] found that 54.5% of individuals were poor sleepers among 894 elderly adults in Zagreb nursing homes. Tsai et al [34] found that 46.4% of participants reported poor sleep quality among 196 elderly AOR, adjusted odds ratio; RERI, the relative excess risk due to interaction; AP, the attributable proportion due to interaction; S, the synergy index.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is comparable to those of other previous studies conducted in elderly adults living in nursing homes in Turkey [31,32]. However, with a similar population, the same institutional setting and measurement tool, Stefan et al [33] found that 54.5% of individuals were poor sleepers among 894 elderly adults in Zagreb nursing homes. Tsai et al [34] found that 46.4% of participants reported poor sleep quality among 196 elderly nursing home residents in Taiwan.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, Eser et al 34 estimated that the prevalence of poor sleep quality was 60.9% among 540 elderly people in Turkey, and a similar study in the same country found that 60.3% of the elderly had poor sleep quality. 23 Lower prevalence was also observed in Zagreb (54.5%) among 894 elderly people, 35 and in Taiwan (46.4%). 36 A reason for this variation in these prevalence estimates may be attributed to differences in study designs with regard to inclusion criteria for participants, and differences in the facilities and medical care used in different nursing homes.…”
Section: Discussionmentioning
confidence: 95%